Effects of neutralizing antibodies on escape from CD8+ T-cell responses in HIV-1 infection. - Wikramaratna, P; Lourenço, J; Klenerman, P; Pybus, O; Gupta, S (Royal Society, 2015)
Despite substantial advances in our knowledge of immune responses against HIV-1 and of its evolution within the host, it remains unclear why control of the virus eventually breaks down. Here, we present a new theoretical framework for the infection dynamics of HIV-1 that combines antibody and CD8(+) T-cell responses, notably taking into account their different lifespans. Several apparent paradoxes in HIV pathogenesis and genetics of host susceptibility can be reconciled within this framework by assigning a crucial role to antibody responses in the control of viraemia. We argue that, although escape from or progressive loss of quality of CD8(+) T-cell responses can accelerate disease progression, the underlying cause of the breakdown of virus control is the loss of antibody induction due to depletion of CD4(+) T cells. Furthermore, strong antibody responses can prevent CD8(+) T-cell escape from occurring for an extended period, even in the presence of highly efficacious CD8(+) T-cell responses.